On the characterization of potentially Κ1,1,s-graphic sequences - Yin, Meng-Xiao; Yin, Jian-Hua; Zhong, Cheng; Yang, Feng (Utilitas Mathematica, 2011)
For given a graph H, a graphic sequence π = (d1, d 2,⋯, dn) is said to be potentially H-graphic if there is a realization of π containing H as a subgraph. In this paper, we characterize the potentially Κ1,1,s-positive graphic sequences for s = 4 and 5, where Κ1,1,s is the 1 x 1 x s complete 3-partite graph. These characterizations imply the values of σ (Κ1,1,s,n) for s = 4 and 5.